The good son a novel - Gruber, Michael 1940- (Henry Holt and Company, 2010)
Somewhere in Pakistan, Sonia Laghari and eight fellow members of a symposium on peace are being held captive by armed terrorists. Sonia, a deeply religious woman as well as a Jungian psychologist, has become the de facto leader of the kidnapped group, while her son Theo, an ex-Delta soldier, uses his military connections to find and free the victims.